Systemic Mechatronic Function Development - Udo Pulm and Ralf Stetter (Proceedings of the Design Society, 2021)
Since decades, researchers are developing methods, tools, and processes for the development of mechatronic systems. In the last decade, this field has widened, including, amongst others, aspects such as cyber-physical systems (CPS) or the internet of things (IoT). Still, little concrete guidance can be identified for engineers who have to decide whether to realize a certain product function mechanically, electronically, through software functions, or with combinations thereof. The goal of the paper is to contribute to the development of guidelines for design engineers in which domain (or in which combination of domains and other areas) to allocate the solution for an engineering problem.